A mixed-methods exploration of social networks, self-efficacy, and life satisfaction in rural Chinese high schools - Ping Zhu; Tingting Wang (Frontiers in Psychology)
IntroductionThis mixed-methods study explored how social networks influence academic self-efficacy and life satisfaction among rural Chinese high school students.MethodsThe study involved 454 students in the quantitative phase, utilizing the Social Network Index (SNI), Academic Self-Efficacy Scale (ASES), and Satisfaction with Life Scale (SWLS). The qualitative phase included interviews with 28 students.ResultsQuantitative results revealed that network centrality (r = 0.34, p < 0.001) and density (r = 0.28, p < 0.001) positively correlated with academic self-efficacy. Network centrality (r = 0.20, p < 0.001) and network size (r = 0.22, p < 0.001) were positively correlated with life satisfaction. Females exhibited higher academic self-efficacy than males [t(452) = 3.52, p < 0.001], and network density increased with grade level [F(2, 451) = 6.78, p = 0.001]. Qualitative themes highlighted supportive friendships as empowering, competitive pressures within dense networks as both motivating and stressful, and broader networks (including family) as vital for well-being.DiscussionThese findings emphasize the dual role of social networks in fostering academic confidence and life satisfaction while also introducing competitive stressors. This is particularly relevant in rural contexts where family support is crucial. Implications include the need to promote supportive peer relationships and mitigate the negative effects of competition.